Yahudi Dalam Zionisme Dan Israel - Samsuri Samsuri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
This paper traces the Judaism teachings as basic of Jewish movements. The Judaism has two meaning as its identity. Firstly, Judaism is a religion. Secondly, it is an ethnic or nation. According to Jacob Neusner, Judaism is a religion that Scripture’s account of Israel as holy people whose life encompasses the experience o f exile and return. In this paper, author tries to explore three streams of the Jewish religion movements— i.e. Reformers, Conservatives, and Orthodox- which influenced the Jewish emancipation’s Europe in l 9th century until Holocaust tragedy on the Second World War. Zionism has risen as a respond to political crisis which fallen to emancipate the Jewish people from the oppressed as long as diaspora period in Europe. Its purpose created the homeland for Israel when Jewish people returned from Diaspora.